Uptake of heavy metals by Moringa oleifera planted in contaminated soil - Jamalludin, Norsuria Mirza (2018)
Phytoremediation is the use of plants to remediate pollutants from soils and this approach has not been widely practiced in Malaysia. This study was conducted in a greenhouse, at the Faculty of Forestry, Universiti Putra Malaysia. The objectives of this study were to determine the potential of Moringa oleifera in removing heavy metals of contaminated soil and to evaluate the heavy metals uptake and translocate in plant parts especially roots, stems and leaves by using an indicator of Translocation Factor (TF) and Bio-concentration Factor (BCF). M. oleifera were germinated at the greenhouse for two months prior transplanting into growth media (soil + heavy metals) for five months. The seedlings were planted on 10 different growth media with replicated for four times (soil + different concentrations of heavy metals) namely; control T0-Control (100% soil), Tl (soil 1kg + 100ppm CuSO4), T2 (soil 1kg + 200ppm CuSO4), T3 (soil 1kg + 300ppm CuSO4), T4 (soil 1kg + 100ppm FeSO4), T5 (soil 1kg + 200ppm FeSO4),T6 (soil 1kg + 300ppm FeSO4), T7 (soil 1kg + 100ppm ZnSO4), T8 (soil 1kg + 200ppm ZnSO4), and T9 (soil 1kg + 300ppm ZnSO4).The results showed that the concentrations of heavy metals among treatments before planting and after harvesting were significant differences. After harvesting,concentration of Cu, Fe and Zn decreased in all treatments where as were very effective in removing the heavy metal which was in T9 (3.110 mg kg-1) for Cu, Fe was in T6 (1046.382mg kg-1) while Zn in T9(42.777 mg kg-1 ). Studies showed that, the highest accumulation of Cu in the plant parts was in root of T3 (1.148mg kg-1) as well as Fe (346.293 mg kg-1) for T6 and Zn(14.085mg kg-1 ) in T9. Bioconcentration Factors (BCF) and Translocation Factor (TF) for the three heavy metals (Cu, Fe and Zn) showed that BCF values were lower than 1, while TF above than 1, indicating that M. oleifera is capable to translocate metals from roots to shoots and this study confirms that this species as a phytoextractor plant.